FAKTOR RISIKO PREDIABETES PADA JEMAAH HAJI DI DKI JAKARTA (ANALISIS DATA SISKOHATKES TAHUN 2023) - Balqis Triaya Dewanti, (2024)
Every year, the prevalence of prediabetes increases, and globally it is estimated that one in three people develops prediabetes. Prediabetes can lead to all causes of death as well as complications of cardiovascular disease, stroke, and chronic kidney failure if not properly prevented. This study aims to identify the factors that influence the incidence of prediabetes among Hajj pilgrims in DKI Jakarta. The study uses a cross-sectional study design with secondary data from Siskohatkes in 2023 and a large sample of 5,615. The prevalence of prediabetes among Hajj pilgrims in DKI Jakarta in 2023 was 39.6%. The results of multivariate analysis showed age (aPR 1.56; 95% CI 1,38-1,78), hypertension (aPR 1.22; 95%CI 1.12-1.33), tryglycerides (aPR 1.20; 95%CI 1.10-1.31), cholesterol high density lipoprotein (HDL) (aPR 1.18; 95%CI 1.07-1.29), body mass index (BMI) (aPR 1.14; 95%CI 1.05-1.24), educational level (aPR 0.69; 95%CI 0.62-0.76) had a relationship with prediabetes incidence among Hajj pilgrism. The risk factors for prediabetes among Hajj pilgrims in DKI Jakarta are age, hypertension, triglycerides, HDL, and BMI